Métodos de fertilización orgánica de camu camu (Myrciaria dubia MC Vaugh H.B.K.) en área inundable de la Amazonía Peruana, Moena Caño-Belén-Iquitos - Abreu Pereira, Patrick Marcelo (2023)
The research was carried out under floodable soil conditions of the Moena Caño Belén experimental field. The objective was to evaluate types of organic fertilization on the productivity and quality of camu camu (Myrciaria dubia) fruit in the floodplain area of Moena Caño-Belén,, evaluating number of flowers/branch, number of fruits/branch, weight of fruits/plant , fruit weight and pulp acidity. The Completely Random Design was used, with 5 treatments and 10 repetitions, and the sampling unit consisted of 1 plant, making a total of 50 plants. The results show that the different methods of organic fertilization did not have a significantly different influence on the yield components, respectively, but they did have a significantly different influence on the average fruit weight, highlighting the domestic compost treatment, as well as the different types of organic fertilization. did not significantly influence the fruit quality components, respectively, in a different way. With the exception of the average weight of the fruit, the hypotheses raised in the characteristics of the yield and quality components of the fruit were not rejected at a probability of committing a type I error of 0.05 and it is recommended to make a better estimate of the behavior of the variables studied. studying the types of organic fertilization but in interaction with the dose factor and considering a greater number of repetitions per treatment